Barriers to implementation of Academia da Saúde program in Santa Catarina - de Paiva Neto F.T. (2019)
© 2019 Universidade Estadual de Maringa. All rights reserved.The Brazilian Ministry of Health created the Academia da Saúde Program (ASP) to contribute to promoting health through the implementation of units for guidance on bodily practices, physical activity and leisure, with a healthy lifestyle as intended outcome. The objective of this study was to identify the perception of physical activity program managers about barriers to the operation of ASP units in Santa Catarina (SC). A cross-sectional study was conducted with 26 managers (61.5% women) of physical activity programs. Information was collected by means of a questionnaire designed for assessing interventions aimed at promoting physical activity in Primary Health Care. Descriptive statistics (mean, standard deviation, absolute and relative frequency) was used for data analysis. Results evidenced as main barriers lack of human resources, lack of support from heads, lack of material conditions, facilities and equipment, as well as lack of standardized instruments for evaluation of actions. It is concluded that organizational, infrastructure and human resources barriers are present in the routine of ASP actions in SC.